Hukum sebagai Alat Rekayasa Sosial: Gagasan Roscoe Pound dan Relevansinya Bagi Reformasi Hukum di Indonesia - Rasji; William Chandra; Marcellius Kirana Hamonangan (CV Rewang Rencang, 2024)
This article aims to examine the concept of law as a tool of social engineering based on Roscoe Pound’s theory and its relevance within the Indonesian legal system. The study employs a normative juridical approach, using conceptual, historical, and comparative methods. Findings show that although Indonesia adopts a civil law system with legalistic tendencies, social engineering through law is still possible via legislative reform and strengthening law as an agent of change. The adapted ideas of Pound by Mochtar Kusumaatmadja and Satjipto Rahardjo indicate that law must remain responsive and adaptive to social demands. This article emphasizes the importance of integrating legal theory with public policy in advancing national legal reform.